THE POLITICS OF JUSTICE-BASED INTERNATIONAL BANKRUPTCY LAW - Soetoto, Erwin Owan Hermansyah (UNISSULA, 2024)
The purpose of this study is to analyze international legal regulations regarding cross-border bankruptcy that are not yet fair, and to analyze international bankruptcy legal policies based on justice that can be applied effectively in a cross-border context. This study uses normative legal research. The results of this study are differences in the application of the territorial principle and the universality principle in various countries can cause injustice to debtors and creditors. The territorial principle can make it difficult for debtors who have separate assets in several countries, so they have to face bankruptcy processes separately in several countries, while the universality principle can cause injustice because creditors can be harmed by the application of the debtor's original law which is more beneficial to the debtor. Restorative justice emphasizes the restoration of losses for the injured party. The restorative justice approach can help reduce conflict in the international bankruptcy process and encourage solutions that prioritize mediation in its resolution. With the restorative justice approach, it is expected to provide justice for all parties.